INITIATIVE PROGRAMS OF LIGHT VEHICLE MANAGEMENT IN ORDER TO SUPPORT ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) IN ZONA 4 REGIONAL 1 SUBHOLDING UPSTREAM PERTAMINA - Kholid Yadi, Moh
Recently, the challenges of oil and gas companies is increasing, beside targeting to generate profits, they must also consider ESG aspects, including efforts to reduce carbon emissions. Subholding Upstream Pertamina (SHU) determine this program as the company's annual achievement targets and is cascaded to become the target of each department. To support this common target, each department must review its respective business processes, what activities that produce carbon emissions, and attempt to find the potential for improvements that can be made. In SCM Department, one of the activities that produces quite high carbon emissions is the provision of light vehicles (LV) which the quantity is more than 440 units of vehicles all around Zona 4. In this context, the selection of optimal alternative fuels that balance efficiency, operations, environmental impacts, and compliance with regulations is very important.